Basic Knowledge and Criteria for Truth - Robiatul Samiah; Maspuroh; Adit Abdul Hanan; Hasnah Nurhalimah (Bibliotheca: Journal of Philosophy, 2025)
Truth is an eternal question for humans in every era. People never finish arguing about it. The basis of truth is that which exists or exists. Truth is only possible if something exists. Philosophy positions itself as a human effort to search for truth. Because one of the meanings of philosophy itself is love of truth. Truth is very important, but the question of truth is very relative, because what may be true today may not necessarily be true tomorrow. The truth is outside of humans, humans just have to search and find it. Therefore truth is determined by external factors, not internal. Thus making truth a target object that is always interesting in the world of philosophy.